Learners' Perspectives on Networked Collaborative Interaction With Native Speakers of Spanish in the US - Lina Lee (Language Learning and Technology, 2004)
In this paper, I discuss a network-based collaborative project that focused on the learning conditions non-native speakers (NNSs) of Spanish perceived to be necessary to satisfactoraly communicate with native speakers (NSs). Data from online discussions, end-of-semester surveys, and final oral interviews are presented and discussed. The results of this study demonstrated that the NNS and NS online collaboration promoted the scaffolding by which the NSs assisted the NNSs in composing meaning (ideas) and form (grammar). In addition, the NNSs praised the unique learning condition of being exposed to a wide range of functional language discourse produced by the NSs. Students perceived that open-ended questions for two-way exchange were meaningful for them because they were encouraged to use specific vocabulary and structures during the discussions. In spite of the positive conditions and benefits created by networked collaborative interaction (NCI), it was found that there were some major issues that are crucial for NCI. This study demonstrates that learners' language proficiency, computer skills, and age differences are important factors to be considered when incorporating institutional NCI as these may linguistically and socially affect the quality of online negotiation and students' motivation toward NCI. Practical ideas for further research are suggested.